Bioactive Coatings Based on Hydroxyapatite, Kanamycin, and Growth Factor for Biofilm Modulation - Oana Gherasim; Alexandru Mihai Grumezescu; Valentina Grumezescu; Irina Negut; Marius Florin Dumitrescu; Miruna Silvia Stan; Ionela Cristina Nica; Alina Maria Holban; Gabriel Socol; Ecaterina Andronescu (MDPI AG, 2021)
The occurrence of opportunistic local infections and improper integration of metallic implants results in severe health conditions. Protective and tunable coatings represent an attractive and challenging selection for improving the metallic devices' biofunctional performances to restore or replace bone tissue. Composite materials based on hydroxyapatite (HAp), Kanamycin (KAN), and fibroblast growth factor 2 (FGF2) are herein proposed as multifunctional coatings for hard tissue implants. The superior cytocompatibility of the obtained composite coatings was evidenced by performing proliferation and morphological assays on osteoblast cell cultures. The addition of FGF2 proved beneficial concerning the metabolic activity, adhesion, and spreading of cells. The KAN-embedded coatings exhibited significant inhibitory effects against bacterial biofilm development for at least two days, the results being superior in the case of Gram-positive pathogens. HAp-based coatings embedded with KAN and FGF2 protein are proposed as multifunctional materials with superior osseointegration potential and the ability to reduce device-associated infections.